Linear IgA bullous dermatosis induced by atezolizumab: a case report - Seba Almutairi; Dana Alessa (PAGEPress Publications, 2024)
Linear IgA Bullous Dermatosis (LABD) is a rare immune-mediated vesiculobullous disease that was reported to be induced by infections or medications. Atezolizumab is a monoclonal antibody targeting programmed cell death ligand-1 (PD-L1), it has been used to treat multiple cancers. Here, we report a case of drug induced LABD following the administration of Atezolizumab.